International african migration to Brazil and its territorialities in Ceara state - Bomtempo, Denise Cristina; Pinto Senna, Kananda Beatriz (Geografares, 2021)
This paper explains the territorialities built in the international migration of Africans to Brazil, especially to Ceara state in the first decades of the 21st century. To support the discussion, the theoretical-methodological path was built from: the selection of concepts, the bibliographic and data survey, and the empirical research. In light of what was investigated, we affirm that in Brazil, the presence of migrants is verified in numerous federative units: São Paulo, Rio Grande do Sul, Santa Catarina, Rio de Janeiro, Ceara, Parana and Minas Gerais. The presence of Africans in Ceara causes multiple migratory territorialities and circularities, since the profiles of individuals in mobility are diverse (students, workers and investors). In a first phase of the migration process, the subjects settled residence in Fortaleza, Redenção and Acarape, but over time, because they did not return to their country of origin, they circulated through different neighborhoods in Fortaleza and in other Ceara cities. It is worth mentioning that the presence of these migrants, according to the empirical profile evidenced, has increased significantly, demonstrating the role of Ceara’s centrality in the new routes and migratory dynamics configured in the Brazilian territory.